Extending the Queen Bee Effect: How Hindustani Workers Cope with Disadvantage by Distancing the Self from the Group. (September 2015) - Derks, Belle; van Laar, Colette; Ellemers, Naomi; Raghoe, Gauwrie; Stroebe, Katherine; de Lemus, Soledad
<x xml:space="preserve">Abstract</x> Previous research revealed that one way by which members of minority groups resist disadvantage is through strategic "self‐group distancing" by evaluating this group negatively, describing themselves according to outgroup stereotypes and supporting the status hierarchy, hereby limiting societal change. Drawing upon recent work on the Queen Bee phenomenon among women at work, we explain self‐group distancing as a coping response of low identified minority employees who experience social identity threat. Whereas queen bee behavior is often discussed as a response typical for women, new experimental data are presented revealing similar responses among ethnic minority employees. In parallel to queen bees, low identified Hindustanis reported less positive ingroup affect and presented themselves as more stereotypically Dutch when reminded of ethnic bias—but not in a control condition. This suggests that the Queen Bee phenomenon exemplifies a more generic individual mobility response to group disadvantage experienced by minority groups at work.